DIGESTATE RECYCLING TECHNICALLY ECONIMOC JUSTIFICATION - Sutre, Karolīna; Teirumnieka, Ērika (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The paper contains general information abot evaluate the production of biogas by-products recycling use possibilities, digestate processing and digestate recycling, the methods of its use possibilities and economic side. Also digestate positive benefits and negative aspects.